Synthesis of amorphous CoMoSx/g-C3N4 photocatalyst for enhanced solar hydrogen production - Yeo, Loo Pin (2016)
Fossil fuel dependency has raised serious environmental and resource depletion concerns. Amidst news of worsening climate conditions and air pollution, technologies to harness renewable energy have garnered great interest. Photocatalytic water splitting to produce hydrogen as an alternative clean fuel has been widely researched as a potential solution. Polymeric graphitic carbon nitride (g-C3N4) has been identified as a promising photocatalyst with a suitable electronic band structure for water splitting. However, the hydrogen evolution activity of pure g-C3N4 is limited due to low light absorption and high rate of electron-hole pair recombination. Coupling g-C3N4 with cocatalysts such as metal sulfides has greatly improved photocatalytic activity. This study aims to further enhance photocatalytic activities by incorporating novel heterobimetallic sulfide cocatalysts instead of the monometallic sulfide cocatalysts that have been frequently studied. g-C3N4 with heterobimetallic CoMoSx cocatalysts were prepared along with MoS2/g-C3N4, CoS/g-C3N4 and pure g-C3N4 samples via hydrothermal method to facilitate comparison of their hydrogen evolution activity. The properties of the photocatalysts were characterised by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet-Visible Spectroscopy (UV-Vis) and Photoluminescence (PL) Spectroscopy. TEM and PL results indicate that the morphological differences in CoMoSx/g-C3N4 can further reduce rate of electron-hole pair recombination, thus enhancing hydrogen evolution. CoMoSx/g-C3N4 showed the greatest hydrogen evolution rate of 1.02 μmol h-1 which is approximately 11.4 times improved compared to the photocatalytic activity of MoS2/g-C3N4.